Controlled swollen and drug release from urea-cross-linked polyether/siloxane hybrids - Santilli, Celso Valentim [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Lopes, Leandro [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Oliveira, Anselmo Gomes de [UNESP] (Laboratório Nacional de Luz Síncrotron, 2009)
From a simple synthesis method we produced transparent ureasil cross–linked polyether (poly(ethylene oxide), PEO, or poly(propylene oxide), PPO) networks, whose designed inter cross–linking distance and tunable swellability was assessed by small angle X–ray scattering on the D11A–SAXS1 beamline of the LNLS. We demonstrated that the controlled drug release from swellable hydrophilic ureasil–PEO materials can be sustained during some days, while from the unswellable ureasil–PPO ones, during some weeks. This outstanding feature conjugated with the biomedically safe formulation of the ureasil cross–linked polyether/siloxane hybrid widen their scope of application to include the domain of soft and implantable drug delivery devices.